Intracolonic Neuropeptide Y Y1 Receptor Inhibition Attenuates Intestinal Inflammation in Murine Colitis and Cytokine Release in IBD Biopsies. Issue 4 (6th October 2021) - Chandrasekharan, Bindu; Boyer, Darra; Owens, Joshua A; Wolfarth, Alexandra A; Saeedi, Bejan J; Dhere, Tanvi; Iskandar, Heba; Neish, Andrew S
Abstract: We have demonstrated that neuropeptide Y (NPY) can regulate pro-inflammatory signaling in the gut via cross-talk with the pro-inflammatory cytokine tumor necrosis factor (TNF). Here, we investigated if selective blocking of NPY receptors, NPY1R or NPY2R, using small molecule non-peptide antagonists (BIBP-3222 for NPY1R and BIIE-0246 for NPY2R) in the colon could attenuate intestinal inflammation by lowering TNF levels (BIBP - N-[(1R)]-4-[(Aminoiminomethyl)amino-1-[[[(4-hydroxyphenyl)methyl]amino]carbonyl]butyl-α-phenylbenzeneacetamide; BIIE - N-[(1S)-4-[(Aminoiminomethyl)amino]-1-[[[2-(3, 5-dioxo-1, 2-diphenyl-1, 2, 4-triazolidin-4-yl)ethyl]amino]carbonyl]butyl]-1-[2-[4-(6, 11-dihydro-6-oxo-5H-dibenz[b, e]azepin-11-yl)-1-piperazinyl]-2-oxoethyl]-cyclopentaneacetamide). Colitis was induced using dextran sodium sulfate in drinking water for 7 days, or by adoptive T-cell transfer in RAG -/- mice. Colonic biopsies from healthy subjects ( n = 10) and IBD patients ( n = 34, UC = 20, CD = 14) were cultured ex vivo in presence or absence of NPY antagonists (100 µM, 20 h), and cytokine release into culture supernatants was measured by ELISA. Intracolonic administration of BIBP (but not BIIE) significantly reduced clinical, endoscopic, and histological scores, and serum TNF, interleukin (IL)-6, and IL-12p70 in DSS colitis; it also significantly attenuated histological damage and serum IL-6 in T-cell colitis ( P < .05). Intracolonic administration of BIBP significantly reduced TNF and interferon (IFN)-γ release from UC biopsies, whereas BIIE downregulated only IFN-γ ( P < .05). BIBP significantly reduced TNF and interferon (IFN)-γ release from UC biopsies, whereas BIIE downregulated only IFN-γ ( P < .05). Our data suggest a promising therapeutic value for NPY1R inhibition in alleviating intestinal inflammation in UC, possibly as enemas to IBD patients.